Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Menginap Di Pangeran Beach Hotel Padang - Ardila Susanti; Yuliana Yuliana (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This study aims to analyze the effect of price and service quality on guests' stay decisions at Pangeran Beach Hotel Padang. This type of research is quantitative research. The population of this study was guests staying at Pangeran Beach Padang with a sample of 93 consumers. The sampling technique uses non probability sampling. Data collection techniques are carried out using questionnaires (questionnaires) with Likert scales that have been tested for validity and reliability. Data from this study was processed using SPSS 25.00. The results of this study show that the price is included in the sufficient category with a percentage of 48.38%, the quality of service is in the sufficient category of 59.13%. The variable of overnight decision is in the sufficient category, which is 88.17%. Obtained R Square value of 0.021, meaning that the influence of the price variable (X1) on the decision variable to stay (Y) was 2.1% while 97.9% was influenced by other factors. The R Square value is 0.033, meaning that the influence of the service quality variable (X2) on the decision to stay (Y) is 3.3% while 96.7% is influenced by other factors. The effect of price (X1) and service quality (X2) affects the decision to stay (Y), the R Square value is 0.097, meaning that the influence of price variables (X1) and service quality (X2) on consumer satisfaction variables (Y) as much as 9.7% while 90.3% is influenced by other factors that were not studied in this study. And obtained the value of F calculate 1.242 with sig. 0.000 < 0.05.